MODAL SOSIAL DALAM PEMANFAATAN BUAH TENGKAWANG DI HUTAN ADAT PIKUL - Dewita Dewita; Emi Roslinda; Siti Masitoh Kartikawati (Tengkawang : Jurnal Ilmu Kehutanan, 2020)
Pikul customary forest has the potential of tengkawang that was abundant and utilized by the community around the forest to fulfill their daily needs. This study aimed to determine community social capital consists of cognitive and structural social capital and the relationship of social capital how to use tengkawang fruit in the Pikul indigenous forest. This study used the concept survey methods, with data collection techniques with interviews used questionnaires and in-depth interviews with key respondents. Respondents in this study were Melayang Hamlet community who used tengkawang fruit intentionally. The magnitude level of social capital used the value interval equation and the relationship of social capital was analyzed of Sperman rating coefficient test. The results showed the cognitive social capital and the structural social capital were both classified as "high". The relationship of social capital which used of tengkawang has a direct and strong relationship, the two elements of Cognitive and structural social capital were very significant and relate with the way how to use tengkawang. The real correlation occurred in the form of a positive correlation that showed the higher level of structural social capital and cognitive social capital formed, which better used of tengkawang fruit in the Pikul customary forest.Keywords: social capital, tengkawang fruit, Pikul costomary forestAbstrakHutan Adat Pikul memiliki potensi tengkawang yang sangat melimpah. Jenis ini dimanfaatkan masyarakat sekitar hutan untuk memenuhi kebutuhan hidup. Penelitian ini bertujuan mengetahui modal sosial masyarakat yang terdiri atas modal sosial kognitif dan struktural dan hubungan modal sosial terhadap pemanfaatan buah tengkawang di hutan Adat Pikul. Penelitian ini menggunakan metode survei, melalui teknik wawancara menggunakan kuesioner dan wawancara mendalam kepada responden kunci. Responden dalam penelitian ini adalah masyarakat Dusun Melayang yang memanfaatkan buah tengkawang. Tingkat modal sosial masyarakat dianalisis menggunakan persamaan selang nilai. Sementara itu hubungan modal sosial dianalisis menggunakan uji koefisien Peringkat Sperman. Hasil penelitian menunjukan bahwa modal sosial kognitif serta modal sosial struktural tergolong “tinggi”. Hubungan modal sosial terhadap pemanfaatan tengkawang memiliki hubungan yang searah dan kuat. Kedua unsur modal sosial Kognitif dan struktural berhubungan sangat nyata terhadap pemanfaatan tengkawang. Korelasi nyata yang terjadi berupa korelasi positif yang menunjukkan semakin tinggi tingkat modal sosial struktural dan modal sosial kognitif yang terbentuk, semakin baik pula pemanfaatan buah tengkawang di hutan Adat Pikul. Kata kunci: Modal Sosial, Buah Tengkawang, Hutan Adat Pikul